2016
DOI: 10.1002/dneu.22419
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptor 5 responses dictate differentiation of neural progenitors to NMDA‐responsive cells in fragile X syndrome

Abstract: Disrupted metabotropic glutamate receptor 5 (mGluR5) signaling is implicated in many neuropsychiatric disorders, including autism spectrum disorder, found in fragile X syndrome (FXS). Here we report that intracellular calcium responses to the group I mGluR agonist (S)-3,5-dihydroxyphenylglycine (DHPG) are augmented, and calcium-dependent mGluR5-mediated mechanisms alter the differentiation of neural progenitors in neurospheres derived from human induced pluripotent FXS stem cells and the brains of mouse model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 62 publications
2
54
0
Order By: Relevance
“…Using Fura-2-based fluorescence recordings, we monitored [Ca 2+ ] i responses in all or most individual cells migrating out from the neurosphere ( Fig. 1B) (23,30). We observed that the proportion of glutamate-responsive cells was increased in FXS neurospheres when compared to controls at both time points studied (Fig.…”
Section: Increased Differentiation Of Cells Expressing Ampars Is Seenmentioning
confidence: 94%
See 2 more Smart Citations
“…Using Fura-2-based fluorescence recordings, we monitored [Ca 2+ ] i responses in all or most individual cells migrating out from the neurosphere ( Fig. 1B) (23,30). We observed that the proportion of glutamate-responsive cells was increased in FXS neurospheres when compared to controls at both time points studied (Fig.…”
Section: Increased Differentiation Of Cells Expressing Ampars Is Seenmentioning
confidence: 94%
“…In the neurosphere model, radial glia cells first appear from the differentiating neurospheres; differentiation of neuron-like cells closely follows radial glia during the first days of differentiation (30,49). We have previously shown that [Ca 2+ ] i responses through mGluR5 correlate with radial glia and functional AMPA/kainate (KA) receptor expression in many cells as soon as the first day of differentiation, whereas responses to N-methyl-d-aspartate (NMDA) are detectable in measurable amounts of cells after 7 days of differentiation (12,23,30,49). We sequentially exposed FXS and control neurospheres to (S)-3,5-dihydroxyphenylglycine (DHPG; a specific agonist of type I mGluR) and KA (an agonist of AMPA and KA receptors) at day 1 of differentiation and to KA and NMDA at day 7 of differentiation.…”
Section: Increased Differentiation Of Cells Expressing Ampars Is Seenmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient-derived iPSC lines (STAT3 K392R cells) were then differentiated into pancreatic progenitors using a four-stage protocol based on previously published reports (Mfopou et al, 2010;Nostro et al, 2011;Toivonen et al, 2013b) with minor modifications to achieve efficient differentiation from all the cell lines ( Figure S2A; Supplemental Experimental Procedures). Healthydonor iPSC line HEL47.2 (Trokovic et al, 2015a), HEL24.3 (Trokovic et al, 2015b), HEL46.11 (Achuta et al, 2017), and human embryonic stem cell line H9 (Thomson et al, 1998) were used as controls.…”
Section: Patient-derived Ipscs With An Activating Stat3 Mutation Diffmentioning
confidence: 99%
“…As Zhu et al suggest, the original monogenic models can then serve as a form of positive control against which more complex models can be compared. iPSC models have already been successfully used to identify cellular and molecular dysfunction that occurs in other forms of monogenic ASD-related disorders, including fragile X syndrome [21][22][23][24], Timothy syndrome [25][26][27][28], Rett syndrome [29][30][31][32], tuberous sclerosis [33][34][35][36], and neurofibromatosis type 1 [37][38][39][40]. As more monogenic models are added to the list, in vitro phenotypes can be compared and contrasted between the models to better understand the phenotypes from autism models with a more complex etiology.…”
Section: Introductionmentioning
confidence: 99%